2016
DOI: 10.1155/2016/7950690
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Target Size and Test Distance on Stereoacuity

Abstract: Target size and test distance effects on stereoacuity were investigated in 24 subjects using a three-dimensional monitor. Examination 1: Target Size Effects. The test distance was 2.5 m for 0.1°, 0.2°, 0.5°, and 0.9° target sizes; crossed parallax was presented in 22-second units. Average stereoacuity values for 0.1°, 0.2°, 0.5°, and 0.9° target sizes were 59.58 ± 14.86, 47.66 ± 13.71, 41.25 ± 15.95, and 39.41 ± 15.52 seconds, respectively. Stereoacuity was significantly worse with a 0.1° target than with 0.2°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…These might be an effect of different circle size and viewing distance. 20 The results demonstrate high sensitivity of Titmus for distance VA, near VA and color perception. These results are relevant to a previous study by Horberry TJ et al, 21 which found that Titmus had overall 82.1% sensitivity and 62.5% specificity.…”
Section: Discussionmentioning
confidence: 73%
“…These might be an effect of different circle size and viewing distance. 20 The results demonstrate high sensitivity of Titmus for distance VA, near VA and color perception. These results are relevant to a previous study by Horberry TJ et al, 21 which found that Titmus had overall 82.1% sensitivity and 62.5% specificity.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have reported conflicting results between stereo thresholds and viewing distances. Some reported no correlation between stereo threshold and testing distances [29], while others found a more superior stereopsis at far [30]. Nonetheless, these results vary with the types of tests.…”
Section: Discussionmentioning
confidence: 99%